Analysis of The Causes of Delay Completion of Development Projects Workshop Facility - Bekb, Melak, East Kalimantan - Hamonangan Girsang; Refianda Eki Putra; Irriene Indah Susanti; Yopi Lutfiansyah (NAROTAMA UNIVERSITY, Indonesia, 2022)
Construction projects often suffer from poor performance in terms of execution time management. This is a problem that must be taken seriously. When a delay occurs in a project, there will be additional costs that must be incurred outside the contract and can cause losses for the parties involved, especially the construction contractor. Therefore, it is necessary to pay more attention to the delay in implementation time. The research method used in this research is descriptive quantitative by determining the research variables based on previous journals. Supported by the distribution of phase 1 questionnaires and phase 2 questionnaires which were distributed to 40 respondents related to the Facility Workshop development project located in Melak, East Kalimantan. The questionnaire analysis was assisted by the SPSS version 25 program. The analyzes used were Validity Test, Reality Test, Descriptive Statistical Analysis, Normality Test, Multiple Regression Test, T Test and F Test. From this study, the factors causing delays based on descriptive statistical analysis that meet the requirements of the T-test are material factors (X1), with the indicator